Digital Transformation and Technology Management: A Qualitative Analysis of Organizational Capabilities Strengthening - Mufi Agung Wibowo; Abdul Aziz; Irsal Fauzi; Ari Siswati (Manunggal Halim Jaya, 2026)
This study aims to analyze the role of technology management in improving organizational performance by strengthening innovation and organizational capabilities. Rapid technological developments require organizations to not only adopt technology but also manage it strategically to create value and competitive advantage. The research approach used was qualitative with an exploratory design. Data were obtained through in-depth interviews, observations, and documentation studies of informants directly involved in organizational technology management. Data analysis was conducted using thematic coding techniques to identify key patterns and themes. The results show that planned technology management aligned with organizational strategy plays a crucial role in driving innovation, strengthening organizational capabilities, and improving performance sustainably. Effectively managed digital transformation supports operational efficiency and quality decision-making. This study provides theoretical contributions to the development of technology management studies and practical implications for organizational leaders in formulating adaptive technology management strategies in the era of digital transformation.